Uso de plantas medicinais no tratamento de enfermidades do sistema urogenital na Paraíba - Lins Filho, João Alberto (2023)
Medicinal plants have been used over the years in different locations around the world in the treatment of various diseases. Related to pathologies of the urogenital system, the present research aims to register the species of medicinal plants that are known and used in the treatment of urinary infection, urinary incontinence, chronic kidney disease, prostatic hypertrophy, cancer of the male and female urogenital tract and kidney stones. , by patients seen at the outpatient clinic in the wards of the Hospital Universitário Lauro Wanderley - HULW-UFPB, patients seen at the Espaço Saúde offices located in the municipalities of Guarabira and João Pessoa, and urologists. Semi-structured interviews were carried out with patients from the outpatient clinic, private and public offices and urologists, highlighting 61 botanical species used in the treatment of the evaluated pathologies. In general, the practice is currently developed in greater representativeness by patients, urologists do not usually indicate the use of medicinal plants in the treatment of the evaluated diseases, however most do not contraindicate it. In terms of the number of species, the families stand out: Lamiaceae and Cucurbitaceae, among the vegetative parts mentioned are the leaf, root, bark, fruit and seed. In terms of the aforementioned preparation methods, we have tea, juice, sauce, bottled, in natura and pills/capsules/powder. The species Phyllanthus niruri, Cnidoscolus urens and Cucurbita moschata present high numbers of citations for both evaluated groups. Regarding the general, potential and current utility value of P. niruri species, it was highlighted. Considering the popular practice of using medicinal plants, the recognition of these by the Ministry of Health and the unpreparedness of certain health professionals in dealing with the subject, studies are needed capable of recognizing the species used by the populations and the respective practices involved, as well as how to diagnose the efficiency or not of these traditional medicines, in order to prepare health professionals to point out species that can serve as an alternative form of use in the treatment of diseases that affect the urogenital system.